Dampak Telemedisin terhadap Tingkat Kepuasan Pasien di Beberapa Negara Maju dan Berkembang: Tinjauan Sistematis - Salsabilla Dyah Puspitasari; Anna Wahyuni Widayanti; Susi Ari Kristina (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Telemedicine is a telecommunication technology in healthcare that has expanded rapidly, especially during COVID-19. Its implementation varies between developed and developing countries, raising questions about its impact on patient satisfaction and the factors influencing it. This study aims to evaluate the impact of telemedicine on patient satisfaction across developed and developing countries and to identify key factors influencing satisfaction to inform improvements in telemedicine delivery models. The systematic review was conducted using PubMed, Scopus, and Web of Science databases. The search utilized keywords related to telemedicine and patient satisfaction. The inclusion criteria focused on peer-reviewed articles published between 2020 and 2025, resulting in 14 studies (seven from developed countries and seven from developing countries) being analyzed. Data were extracted and synthesized following the PRISMA guidelines. The analysis identified 14 eligible studies. The findings indicate that telemedicine generally has a positive impact on patient satisfaction, with high satisfaction levels reported across various settings. For example, studies from Sweden and India reported that approximately 78-93% of patients expressed satisfaction or willingness to reuse the telemedicine service. However, several challenges were identified, particularly in developing countries such as Indonesia and the Philippines, including service costs, limited digital infrastructure, and low technological literacy